Quantifying spatiotemporal gradient formation in early Caenorhabditis elegans embryos with lightsheet microscopy. (20th May 2020) - Benelli, Rebecca; Struntz, Philipp; Hofmann, Dirk; Weiss, Matthias
Abstract: Major steps in embryonic development, e.g. body axes formation or asymmetric cell divisions, rely on symmetry-breaking events and gradient formation. Using three-dimensional time-resolved lightsheet microscopy, we have studied a prototypical example for self-organized gradient formation in the model organism Caenorhabditis elegans . In particular, we have monitored in detail the formation of a concentration and mobility gradient of PIE-1 proteins as well as the partitioning behavior of vital organelles prior to the first, asymmetric cell division. Our data confirm the emergence of a concentration gradient of PIE-1 along the embryo's anterior–posterior (AP) axis but they also reveal a previously unseen depletion zone near to the cell cortex that is not present for MEX-5 proteins. Time-resolved spatial diffusion maps, acquired with SPIM-FCS, highlight the successive emergence of a mobility gradient of PIE-1 along the AP axis and suggest an almost linear decrease of fast diffusing PIE-1 proteins along the AP axis. Quantifying the subordinated dissemination of vital organelles prior to the first cell division, i.e. gradient formation on larger length scales, we find a significant asymmetry in the partitioning of the endoplasmic reticulum and mitochondria to the anterior and posterior part of the cell, respectively. Altogether, our spatiotemporally resolved data indicate that current one-dimensional model descriptions for gradient formation during C. elegans embryogenesis, i.e. a mere projection to the AP axis, might need an extension to a full three-dimensional description. Our data also advocate the use of lightsheet microscopy techniques to capture the actual three-dimensional nature of embryonic self-organization events.